Downton Abbey. Season 4 - Evans, David, (Director); Morshead, Catherine; Bonneville, Hugh; Carmichael, Laura, 1986-; Carter, Jim, 1948- ([Place of publication not identified] : [publisher not identified], 2013)
Follows the lives of the aristocratic Crawley family and their servants as they deal with social and personal changes after the end of World War I.
Stereo, wide screen 1.66:1.
Features: additional footage.
Hugh Bonneville, Laura Carmichael, Jim Carter, Brendan Coyle, Michelle Dockery, Joanne Froggatt.
Originally broadcast on television in 2013.
TV rating: Not rated.
Closed-captioned.
Keywords: Aristocracy (Social class) -- England -- Drama; Country life -- England -- History -- 20th century -- Drama; Household employees -- England -- Drama; England -- Social conditions -- 20th century -- Drama; Historical television programs; Television series; Fiction television programs; Video recordings for the hearing impaired